A Case Study : A Short Term Art Therapy Intervention For A Child Victim To Bullying - Matthews, Ffyona (1998)
This single case study of a child bullied at school investigates whether a short-term, individual Art therapy intervention, within a school that runs an anti-bullying program, will ease the effects of bullying in that child. The subject is a 10 year old girl referred as being school avoidant due to being bullied. The intervention encouraged expression of emotions, fears and worries about the bullying, an- understanding of the bullying and its effects, exploration of alternative responses to being bullied and therapeutic support to help empower, build self-esteem, lower depression, loneliness, stress, and unhappiness at school. The intervention involved six one hour long, child focused, directive art therapy sessions and one follow-up session. In addition meetings between caregivers, school psychologist and researcher were held before and after the intervention the effectiveness of the program was evaluated by comparing pre and post results on the effectiveness of the program was evaluated by comparing pre and post results on the following: interviews with the caregivers before and after the intervention: The children’s Depression Inventory (CDI: self portraits of the child discussed with the child as projective material: “The Feeling Thermometer” of how the child feels about school, and the child's attendance at school. Outcomes included a reduction in school avoidance ability to identify affect, changes in the child’s portrayal of herself, and improve family relationships. The child’s mother, school psychologist, principal and the child herself reported benefits. The child was not found to be depressed in the CDI and this was unchanged at completion of the study